IMPROVING STUDENTS’ ACHIEVEMENT IN LEARNING ECONOMICS THROUGH THINK PAIR SHARE (TPS) TYPE COOPERATIVE MODEL AT MAN 1 WEST ACEH - Kemala Dewi (Pedagogi: Jurnal Ilmiah Pendidikan, 2023)
This study aimed to find out: the application of the Think Pair Share (TPS) cooperative learning model in improving students’ achievement in learning Economics in Year XIl IPS-2 of MAN 1 West Aceh. The research method used was classroom action research (CAR), which consisted of 2 cycles. Data analysis used a descriptive comparative analysis technique by comparing the initial conditions with the results achieved in each cycle, and a qualitative descriptive analysis of the results of observations by comparing the results of observations and reflections on cycle I and cycle II. With the application of the Think Pair Share (TPS) Cooperative Learning Model in the basic competencies of recording document transactions into Closing Journals for students of Year XIl IPS-2 of MAN 1 West Aceh in the 2022/2023 academic year. At the end of cycle II it was found out that there has been an increase in the class average of 25.00%, that was, from the initial condition test average of 58.08 to 73.46. Meanwhile, there was an increase in students’ learning completeness of 30.77%, from the initial conditions that had been completed only 6 students to 19 students. Thus, the majority of students in Year XI IPS-2 of MAN 1 West Aceh in the second semester of the 2022/2023 school year have experienced an increase in learning outcomes in the basic competence to close income statement accounts and private accounts in the statement of changes in equity.